m6A Regulator-Mediated RNA Methylation Modification Patterns Regulate the Immune Microenvironment in Osteoarthritis - Duan, Yang; Yu, Cheng; Yan, Meiping; Ouyang, Yuzhen; Ni, Songjia (Frontiers in Genetics, 2022)
Epigenetic regulation, particularly RNA n6 methyl adenosine (m6A) modification, plays an important role in the immune response. However, the regulatory role of m6A in the immune microenvironment in osteoarthritis (OA) remains unclear. Accordingly, we systematically studied RNA modification patterns mediated by 23 m6A regulators in 38 samples and discussed the characteristics of the immune microenvironment modified by m6A. Next, we constructed a novel OA m6A nomogram, an m6A-transcription factor-miRNA network, and a drug network. Healthy and OA samples showed distinct m6A regulatory factor expression patterns. YTHDF3 expression was upregulated in OA samples and positively correlated with type II helper cells and TGFb family member receptors. Furthermore, three different RNA modification pat-terns were mediated by 23 m6A regulatory factors; in Mode 3, the expression levels of YTHDF3, type II T helper cells, and TGFb family member receptors were upregu-lated. Pathways related to endoplasmic reticulum oxidative stress and mitochondrial autophagy showed a strong correlation with the regulatory factors associated with Mode 3 and 23 m6A regulatory factors. Through RT-qPCR we validated that SREBF2 and EGR1 as transcription factors of YTHDF3 and IGF2BP3 are closely as-sociated with the development of OA, hsa-miR-340 as a miRNA for YTHDF3 and IGF2BP3 was involved in the development of OA. Overall, the constructed nomo-gram can facilitate the prediction of OA risk.